Assessing the possibility of solidification and stabilization of pyrite cinder by using quicklime and fly ash - Kerkez, Djurdja; Tomašević Pilipović, Dragana; Bečelić-Tomin, Milena; Slijepčević, Nataša; Rađenović, Dunja; Leovac Maćerak, Anita; Dalmacija, Božo (Journal of Engineering & Processing Management, 2019)
The aim of this study was to determine the possibility of using two low-cost binders, quicklime and fly ash for the solidification/stabilization (S/S) of pyrite cinder. Pyrite cinder, used in this study, represents a remnant from sulfuric acid production in fertilizer factory IHP “Prahovo” A.D. (Serbia), and has a very high toxic metal content. High contents and leachability of copper, lead and zinc make this waste material hazardous, representing an extraordinary risk to the environment. In order to determine the leaching behavior of the S/S mixtures, four single-step leaching tests were performed, each one having a different sort of leaching fluid (deionized water, inorganic and organic acidic solutions). X-ray diffraction (XRD), scanning electron microscope (SEM) and energy dispersive X-ray analyzer (EDS) were implemented to elucidate the mechanisms responsible for immobilization of Cu, Pb and Zn. Overall, the test results indicated that S/S treatment using both quicklime and fly ash was effective in immobilizing these metals, especially when there is a higher share of binder present. Treated waste can be safe for disposal and even considered for “controlled utilization”. Furthermore, the use of fly ash for S/S treatment of pyrite cinder solves the disposal problems of two waste types, as it also represents a secondary industrial product.